Manajemen Pengelolaan Dana Masjid Jami Assa'adah Kelurahan Thehok Kota Jambi - Indri Prihastuti; A A Miftah; Mohammad Orinaldi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Mosque fund management is an important part of carrying out development activities and all aspects regarding existing activities. Mosques obtain funds from various sources, the large amount of funds donated to the mosque requires good fund management, one of the characteristics of good management is the transparency and accountability possessed by every mosque administrator. The mosque has various functions including as a place of worship, a place to conduct religious education, a place for deliberation, a place for consultation, a place for youth activities, a place for alms, zakat and infaq. The main problem in this study is that the Assa'adah Mosque is used for congregational prayer. Apart from congregational prayer, the mosque also needs community development activities in prospering the mosque. Activities at the mosque certainly require funds to carry out various activities. Therefore, this study aims to determine the management of funds owned by the mosque. The focus of the research to be studied is the mosque fund management system and the utilization of mosque funds. This research uses a qualitative descriptive approach, which produces data in the form of words or actions, both written and written, where data is taken by interview, documentation and data taken from the Assa'adah Mosque. The results showed that the mosque fund management system at the Jami 'Assa'adah Mosque uses financial functions, namely planning (planning), (Organizing), (Actuating), (Controlling). The management of mosque funds has several things that are of concern, namely the fund receipt system, the fund storage system, the fund reporting system, and the fund expenditure system. Mosque management provides guidance on mosque management in terms of three fields, namely idarah management as a form of management consisting of mosque management, secretariat, and mosque fund management. Imarah management as a center of worship, education and community empowerment. Then riayah management as the physical maintenance of the mosque.